Analyzing Socially Shared Regulation of Learning during Cooperative Learning and the Role of Equal Contribution: A Grounded Theory Approach - Loes Hogenkamp; Alieke M. van Dijk; Tessa H. S. Eysink (MDPI AG, 2021)
Although cooperative learning is an effective instructional method, it cannot be taken for granted that students will gain new knowledge when engaging in a cooperative activity. Even if cooperative learning is effectively designed, problems might arise regarding cognitive, behavioral and motivational aspects of learning. For students to gain knowledge, cognition, metacognition, behavior and motivation should be collectively regulated by the group, which is called the socially shared regulation of learning (SSRL). However, up until now, there has been no consensus about how SSRL is manifested during cooperative learning. This study investigated how SSRL is manifested during cooperative learning by means of a grounded theory approach. This was done to identify what is necessary for effective SSRL and what its consequences are. A theoretical model was built based on the data in order to portray these prerequisites and consequences of SSRL. This study also investigated whether equal participation fostered SSRL. In this study, participants were students from the fourth, fifth and sixth grades of elementary school, working together in groups of four (n = 104). The data indicated that SSRL is a rare process, the absence of which caused less structured collaboration in groups who were not prompted to participate equally.